Utility of Free Fibula Flap With an Extended Banana-shaped Skin Paddle for Oro-mandibular Reconstructions - Atsumori Hamahata, MD, PhD; Hisato Konoeda, MD, PhD; Satoshi Shirakura, MD, PhD; Kazuhiro Yagihara, MD, PhD; Hiroyuki Sakurai, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. The free fibula flap is a common technique for mandibular bone defects. However, its limited skin paddle is disadvantageous in cases with significant soft-tissue defects. A free fibula dual-skin paddle flap is used for medium-sized soft-tissue defects. Just as the anterolateral thigh flap can be extended through linking vessels, so the peroneal skin flap can be extended to the adjacent proximal area through linking vessels. This has led to the development of the free fibula banana-shaped flap. From 2021 to 2023, 8 patients, with an average age of 68.1 years, underwent head and neck reconstructive surgery using the free fibula banana-shaped flap at the Saitama Cancer Center in Japan. Their primary disease, defect sites, flaps, bone size, and postoperative complications were analyzed retrospectively. The blood flow of the flap was examined using intraoperative indocyanine green imaging. All 8 patients had successful operations with only 1 partial necrosis of the flap tip. Four patients had buccal mucosa cancers, 3 had osteoradionecrosis of the jaw, and 1 had lower gingival cancer. The flap size averaged 25.0 ± 3.0 cm (long axis) and 4.1 ± 0.4 cm (short axis), with a transplanted bone length of 8.4 ± 1.9 cm. The number of perforators was 1–3 in the distal to the central area. All flaps’ microcirculation was confirmed with intraoperative indocyanine green imaging; the average time was 3 minutes 59 seconds. Postoperative complications included 1 surgical site infection and 1 minor salivary leak. The free fibula banana-shaped flap is a good option for head and neck reconstructive surgery in medium-sized soft-tissue defects with mandibular bone defects.